RILEM 252-CMB Symposium Chemo-Mechanical Characterization of Bituminous Materials - Poulikakos, Lily D.; Cannone Falchetto, Augusto; Wistuba, Michael P.; Hofko, Bernhard; Porot, Laurent; Di Benedetto, Hervé (RILEM Bookseries, 2019)
This volume contains the Proceedings of the RILEM TC 252-CMB International Symposium on the Chemo-Mechanical Characterization of Bituminous Materials. The Symposium was attended by researchers and practitioners from different fields presenting the latest findings in the chemical, mechanical, and microstructural characterization of bituminous materials. The book offers new and cutting edge papers on innovative techniques for the characterization of bituminous materials, gaining new insights into current issues such as effects of aging, moisture, and temperature. .